2022
DOI: 10.1038/s41467-022-31026-8
|View full text |Cite
|
Sign up to set email alerts
|

Engineered non-covalent π interactions as key elements for chiral recognition

Abstract: Molecular recognition and self-assembly are often mediated by intermolecular forces involving aromatic π-systems. Despite the ubiquity of such interactions in biological systems and in the design of functional materials, the elusive nature of aromatic π interaction results in that they have been seldom used as a design element for promoting challenging chemical reactions. Described here is a well-engineered catalytic system into which non-covalent π interactions are directly incorporated. Enabled by a lone pai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…With the surging interest in controlling molecular aggregations, , noncovalent interactions (NCIs) have been regarded as driving forces in defining and ruling organizations that lead to a wide variety of conformational architectures and thereafter govern the dynamic processes occurring within superstructures. , In particular, π–π stacking between aromatic rings are common motifs in biomolecular structures and also help understand the binding mechanism between the DNA and proteins, , stereoselective organic reactivity, catalyst design, and the stabilization of supramolecular complexes …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the surging interest in controlling molecular aggregations, , noncovalent interactions (NCIs) have been regarded as driving forces in defining and ruling organizations that lead to a wide variety of conformational architectures and thereafter govern the dynamic processes occurring within superstructures. , In particular, π–π stacking between aromatic rings are common motifs in biomolecular structures and also help understand the binding mechanism between the DNA and proteins, , stereoselective organic reactivity, catalyst design, and the stabilization of supramolecular complexes …”
mentioning
confidence: 99%
“…W ith the surging interest in controlling molecular aggregations, 1,2 noncovalent interactions (NCIs) have been regarded as driving forces in defining and ruling organizations that lead to a wide variety of conformational architectures and thereafter govern the dynamic processes occurring within superstructures. 3,4 In particular, π−π stacking between aromatic rings are common motifs in biomolecular structures and also help understand the binding mechanism between the DNA and proteins, 5,6 stereoselective organic reactivity, 7 catalyst design, 8 and the stabilization of supramolecular complexes. 9 Despite its frequent occurrence, picturing the nature of the π−π stacking remains challenging, since it is defined by a subtle balance between competing energetic contributions and is generally contaminated by other types of NCIs (e.g., hydrogen bonds (HBs), 10 halogen bonds 11 ).…”
mentioning
confidence: 99%
“…5 As shown in Figure 1a, we recently designed an effective bifunctional "N−π" catalysis mode to solve this persistent challenge. 6 This requires a πdonor (in red) at C9 in the cinchona alkaloid and a π-acceptor (in blue) close to the stereocenter in the racemic substrates, which enables a desirable noncovalent π-interaction that includes the substrate's stereocenter into the corresponding catalyst−substrate interacting framework and subsequently renders a successful chiral recognition process. 6 After extensive screening of matching π-components, we surprisingly found that the use of an electron-rich carbonyl group in the cinchona alkaloid ligand and an electron-deficient phthalazine moiety in the substrate helps to realize AD-based kinetic resolutions.…”
mentioning
confidence: 99%
“…6 This requires a πdonor (in red) at C9 in the cinchona alkaloid and a π-acceptor (in blue) close to the stereocenter in the racemic substrates, which enables a desirable noncovalent π-interaction that includes the substrate's stereocenter into the corresponding catalyst−substrate interacting framework and subsequently renders a successful chiral recognition process. 6 After extensive screening of matching π-components, we surprisingly found that the use of an electron-rich carbonyl group in the cinchona alkaloid ligand and an electron-deficient phthalazine moiety in the substrate helps to realize AD-based kinetic resolutions. Density functional theory (DFT) calculations proved that a lone pair−π interaction between the carbonyl oxygen of the ligand and the π-auxiliary of the substrate played a key role in the stereoselectivity-determining transition states; besides this crucial NCI, synergistic cooperation of a π−π interaction between the quinoline moiety of the ligand and the trimethoxyphenyl group of the substrate is also present (Figure 1b).…”
mentioning
confidence: 99%
See 1 more Smart Citation